Elaboración y uso del abono orgánico "te de frutas", en la aplicación foliar en cultivos hortícolas - Pinto Tonato, Jennifer Mariuxi (2024)
The organic fertilizer “fruit tea” has the property of increasing the number of microorganisms in the soil, it also provides energy substances, vitamins, amino acids, minerals and is rich in important macro and micro nutrients; It is obtained through the process of fermenting fruits. In the present bibliographic research, the information obtained was paraphrased, summarized and analyzed in order to obtain relevant information on the preparation and use of the organic fertilizer "fruit tea", in the foliar application in horticultural crops. From what was previously detailed, it was determined that fruit fertilizer is a liquid fertilizer rich in nutrients (main elements) as well as vitamins and amino acids that stimulate the development of plants, the formation of flowers and fruits. Organic fertilizers improve the physical, chemical and biological properties of the soil and ensure an important contribution of nutrients and hormones to the foliage of the plants. Plants grown with the application of fruit fertilizer are more vigorous, have intense green leaves, produce higher yields, have better quality, consistency and can be harvested sooner. The doses in foliar applications of the organic fertilizer “fruit tea” on leafy vegetables are 50 ml/20 liters of water; root vegetables: 100 ml/20 liters of water; fruit vegetables: 250 ml/20 liters of water. The best time to apply organic fruit fertilizer is early in the morning until 10 am and then around 4 pm when the sun sets.